Optimal Control Technique of an Induction Motor - Cheikh Oudaa; Ethmane Isselem Arbih Mahmoud; Abdel Kader Kader Mahmoud; Cherif Bilal Djamal Eddine; Bendiabdellah Azeddine (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
The squirrel cage induction motor (IM) has many advantages over other types of electric technique (FOC), classical direct torque control (DTC), and direct torque control with space vector modulation (DTC-SVM) is carried out. The objective of this paper is to decouple the mechanical quantities such as torque and flux in a way similar to the DC motor control. And also to minimize the torque and flux modulation of the IM. Torque oscillations can cause mechanical resonances and consequently acoustic noise, hence damaging the machine. Reducing the switching frequency significantly minimizes switching losses. The DTC-SVM control technique improves the performance of conventional DTC, which is characterized by low torque and flux modulation as well as a fixed switching frequency. Simulation results in MATLAB show that torque and current ripples are reduced with the improved DTC. DTC-SVM used for the traction control system is easy to implement in digital systems and also allows to move the photovoltaic panels according to the position of maximum sunshine to extract the maximum energy with high efficiency from the system.